Vacuum-assisted closure or primary closure with relaparotomy on-demand in patients with secondary peritonitis: a systematic review and meta-analysis - Pooya Rajabaleyan; Pedja Cuk; Sören Möller; Niels Qvist; Mark Bremholm Ellebæk (World Journal of Emergency Surgery)
Abstract Background Secondary peritonitis is a serious condition with significant morbidity and mortality. Its management requires emergency laparotomy for source control. Vacuum-assisted closure (VAC) and primary abdominal closure (PAC) are the main strategies for managing the laparostomy after source control. Despite the increasing use of VAC, concerns persist regarding its complications and long-term outcomes compared with PAC. Methods This systematic review followed PRISMA 2020 and MOOSE. The Cochrane Risk of Bias (RoB 2) tool, MINORS and GRADE framework assessed study quality and evidence certainty. The protocol was registered in PROSPERO (CRD42022304724). A comprehensive search of MEDLINE, Embase, and the Cochrane Library from January 2004 to August 2024 identified studies reporting postoperative outcomes following VAC or PAC after laparotomy for secondary peritonitis. The included studies had to report at least two key outcomes: mortality, postoperative complications, incisional hernia, secondary fascial closure, and hospital or intensive care unit (ICU) length of stay. Results Thirty-three studies including 4,520 patients were analyzed. Mortality was 31.1% in VAC and 22.2% in PAC (p = 0.327). Postoperative complications were higher with VAC (71.0% vs. 39.3%, p = 0.001). Incisional hernia rates were similar (21.3% vs. 20.8%, p = 0.958). Secondary fascial closure rate was significantly lower with VAC (58.1% vs. 85.9%, p < 0.001). VAC patients had longer ICU stays (21.1 vs. 9.7 days, p = 0.04), while hospital stay did not differ. Most studies had a high risk of bias, and GRADE assessment showed low to very low evidence certainty. Conclusion VAC therapy was associated with more postoperative complications, a lower fascial closure rate, and a longer ICU length of stay compared with PAC. Thirty-day mortality rates did not differ between the approaches. However, most of studies included were subject to serious risk of bias and a low level of certainty in evidence.